Roles of macrophage migration inhibitory factor in cartilage tissue engineering. Issue 2 (4th July 2017) - Fujihara, Yuko; Hikita, Atsuhiko; Takato, Tsuyoshi; Hoshi, Kazuto
Abstract : To obtain stable outcomes in regenerative medicine, understanding and controlling immunological responses in transplanted tissues are of great importance. In our previous study, auricular chondrocytes in tissue‐engineered cartilage transplanted in mice were shown to express immunological factors, including macrophage migration inhibitory factor (MIF). Since MIF exerts pleiotropic functions, in this study, we examined the roles of MIF in cartilage regenerative medicine. We made tissue‐engineered cartilage consisting of auricular chondrocytes of C57BL/6J mouse, atellocollagen gel and a PLLA scaffold, and transplanted the construct subcutaneously in a syngeneic manner. Localization of MIF was prominent in cartilage areas of tissue‐engineered cartilage at 2 weeks after transplantation, though it became less apparent by 8 weeks. Co‐culture with RAW264 significantly increased the expression of MIF in chondrocytes, suggesting that the transplanted chondrocytes in tissue‐engineered cartilage could enhance the expression of MIF by stimulation of surrounding macrophages. When MIF was added in the culture of chondrocytes, the expression of type II collagen was increased, indicating that MIF could promote the maturation of chondrocytes. Meanwhile, toluidine blue staining of constructs containing wild type ( Mif+/+ ) chondrocytes showed increased metachromasia compared to MIF‐knockout ( Mif−/− ) constructs at 2 weeks. However, this tendency was reversed by 8 weeks, suggesting that the initial increase in cartilage maturation in Mif+/+ constructs deteriorated by 8 weeks. Since the Mif+/+ constructs included more iNOS‐positive inflammatory macrophages at 2 weeks, MIF might induce an M1 macrophage‐polarized environment, which may eventually worsen the maturation of tissue‐engineered cartilage in the long term. Abstract : In the present study, we examined the roles of MIF in cartilage regenerative medicine. MIF increased the expression of type II collagen in chondrocytes in an autocrine manner, promoting the maturation of tissue‐engineered cartilage. Meanwhile, MIF in chondrocytes could also regulate the phenotype of surrounding macrophages toward an inflammatory state, exacerbating the maturation of transplanted tissues in the long term.